2011
DOI: 10.1186/1471-230x-11-3
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of enteric glia and GDNF during gut inflammation

Abstract: BackgroundThe enteric glia network may be involved in the pathogenesis of inflammatory bowel disease (IBD). Enteric glia cells (EGCs) are the major source of glial-derived neurotrophic factor (GDNF), which regulates apoptosis of enterocytes. The aim of the study was to determine the distribution of EGCs and GDNF during gut inflammation and to elucidate a possible diminished enteric glia network in IBD.MethodsThe expression of glial fibrillary acidic protein (GFAP) in colonic biopsies of patients with IBD, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(133 citation statements)
references
References 18 publications
7
121
0
5
Order By: Relevance
“…Additionally, a coculture of EGC with intestinal epithelial cells increased IEB function (45). Furthermore, there is a reduced distribution of enteric glial cells in uninflamed colon segments of patients suffering from IBD compared with control popula-tions, suggesting that enteric glial cells could play a role in the pathogenesis of intestinal barrier defects in CD or UC (60). All these observations suggest a close interaction between EGCs and enterocytes.…”
Section: Effects Of Enteric Glial Cells On Intestinal Epithelial Barrmentioning
confidence: 66%
“…Additionally, a coculture of EGC with intestinal epithelial cells increased IEB function (45). Furthermore, there is a reduced distribution of enteric glial cells in uninflamed colon segments of patients suffering from IBD compared with control popula-tions, suggesting that enteric glial cells could play a role in the pathogenesis of intestinal barrier defects in CD or UC (60). All these observations suggest a close interaction between EGCs and enterocytes.…”
Section: Effects Of Enteric Glial Cells On Intestinal Epithelial Barrmentioning
confidence: 66%
“…29 von Boyen et al consistently reported a less prominent increase of GFAP (and GDNF) in patients with CD compared with UC. 57 It is tentative to speculate that an altered glial reactivity (as possibly observed in CD) or excessive gliosis (as possibly observed in UC) could contribute to different pathological conditions.…”
Section: Changes In Egcs In Gastrointestinal Diseasesmentioning
confidence: 98%
“…24 Reactive enteric glia, as with reactive astrocytes, display a marked hypertrophy, 25 increased proliferation 26,27 and vary expression of both cytoplasmic 23 and surface proteins 28 under certain conditions. Notably, under pathological conditions, enteric glia can transform into antigen-presenting cells that promote inflammation by attracting immune cells.…”
Section: Mucosal Glia and Barrier Functionmentioning
confidence: 99%